Multiple ESBL-Producing Escherichia coli Sequence Types Carrying Quinolone and Aminoglycoside Resistance Genes Circulating in Companion and Domestic Farm Animals in Mwanza, Tanzania, Harbor Commonly Occurring Plasmids - Seni, Jeremiah; Falgenhauer, Linda; Simeo, Nabina; Mirambo, Mariam M.; Imirzalioglu, Can; Matee, Mecky; Rweyemamu, Mark; Chakraborty, Trinad; Mshana, Stephen E. (Frontiers in Microbiology, 2016)
The increased presence of extended-spectrum beta-lactamase (ESBL)-producing bacteria in humans, animals and their surrounding environments is of global concern. Currently there is limited information on ESBL presence in rural farming communities worldwide. We performed a cross-sectional study in Mwanza, Tanzania, involving 600 companion and domestic farm animals between August/September 2014. Rectal swab/cloaca specimens were processed to identify ESBL-producing Enterobacteriaceae. We detected 130 (21.7%) animals carrying ESBL-producing bacteria, the highest carriage being among dogs and pigs [39.2% (51/130) and 33.1% (43/130), respectively]. The majority of isolates were Escherichia coli [93.3% (125/134)] and exotic breed type [OR (95%CI) = 2.372 (1.460 - 3.854), p-value <0.001] was found to be a predictor of ESBL carriage among animals. Whole-genome sequences of 25 ESBL-producing E. coli were analyzed for phylogenetic relationships using multi-locus sequence typing (MLST) and core genome comparisons. Fourteen different sequence types were detected of which ST617 (7/25), ST2852 (3/25), ST1303 (3/25) were the most abundant. All isolates harbored the blaCTX-M-15 allele, 22/25 carried strA and strB, 12/25 aac(6’)Ib-cr and 11/25 qnrS1. Antibiotic resistance was associated with IncF, IncY, as well as non-typable plasmids. Eleven isolates carried pPGRT46-related plasmids, previously reported from isolates in Nigeria. Five isolates had plasmids exhibiting 85-99% homology to pCA28, previously detected in isolates from the United States. Our findings indicate a pan-species distribution of ESBL-producing E. coli clonal groups in farming communities and provide evidence for plasmids harboring antibiotic resistances of regional and international impact.